Symbolism and Imagism in T.S. Eliot’s “The Waste Land”: An Analytical Approach - Mariwan Hasan; Shnyar Qasm; Lava Zrar (Universitas Tidar, 2022)
Thomas Stearns Eliot is an American author and poet. He was one of the greatest authors and poets of the modern period. Most of his literary works deal with the aftermath of the war, which enabled him to win the noble prize in literature. This paper tackles imagism and symbolism in “The Waste Land”. T.S. Eliot’s life and his works and modernism have been discussed. The importance of using these literary devices is demonstrated. Then it explains the reason Eliot wrote ‘‘The Waste Land’’ and how it is “a personal grouse” in life. The images have been used from the old age to the contemporary age, yet the use of each image in this poem of T.S. Eliot is completely elucidated. Analytical, historical, and textual approaches make this paper provide a clear understanding of imagism and symbolism. A special focus will be put on symbolism and imagism and the pioneer writers who initiated them.